PENDAMPINGAN SELF-MANAGEMENT STRATEGY BAGI PESERTA DIDIK di SMA A. WAHID HASYIM PESANTREN TEBUIRENG JOMBANG - Wiwin Yulianingsih; Meita Santi Budiani; Rofik Jalal Rosyanafi; Rivo Nugroho; Alfina Nelish Zharfana (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service is to assist the implementation of self-management strategy for students in SMA A. Wahid Hasyim at Pesantren Tebuireng Jombang. This is a form of contribution to educational institutions, at the high school level, especially as a form of strategy in self-management of students who are in the final grade class. The targets of this community service are students and homeroom teachers of class XII SMA A. Wahid, Pesantren Tebuireng. The self-management strategy is carried out as an effort to improve time efficiency and self-preparation in forming good self-management by applying self-management methods career management methods, and problem-solving skills. This service activity is carried out by two types of activities that take place simultaneously on September 21 and 22, 2022. The method used is training, the training method has three stages through identification, socialization and evaluation. Follow-up in community service activities at SMA A. Wahid Hasyim Tebuireng is a measure of the success of students who are able to manage themselves by testing their academic potential.